Association Between Gut Microbial Abundance and Sight-Threatening Diabetic Retinopathy - Khan, Rehana; Sharma, Abhishek; Ravikumar, Raghul; Parekh, Avani; Srinivasan, Ramyaa; George, Ronnie Jacob; Raman, Rajiv (Investigative ophthalmology & visual science, 2021)
To study the association between gut microbial abundance and sight-threatening diabetic retinopathy among patients with a history of type 2 diabetes mellitus. An observational case-control study was performed using a sample population of diabetics referred to a tertiary eye institute. Sample subjects were identified as cases if they were diagnosed with sight-threatening diabetic retinopathy and controls if they were not but had at least a 10-year history of diabetes. Fecal swabs for all patients were collected for enumeration and identification of sequenced gut microbes. Statistical analyses were performed to associate the clinically relevant Bacteroidetes to Firmicutes relative abundance ratio (B/F ratio) with sight-threatening diabetic retinopathy and an optimal cutoff value for the ratio was identified using Youden's J statistics. A sample size of 58 diabetic patients was selected (37 cases, 21 controls). No statistically significant difference in the relative abundance among the predominant phyla between the groups were found. In our univariate analysis, the B/F ratio was elevated in cases compared to controls (cases, 1.45; controls, 0.94; P = 0.049). However, this statistically significant difference was not seen in our multivariate regression model. Optimal cutoff value of 1.05 for the B/F ratio was identified, and significant clustering of cases above this value was noted in beta diversity plotting. No difference in gut microbial abundance for any particular phylum was noted between the control and diseased population. Increased gut microbial B/F ratio can be a potential biomarker for the development of sight-threatening diabetic retinopathy among type 2 diabetic patients.